Description of the ootheca of Turbinella laevigata (Mollusca, Gastropoda) - Matthews Cascon, Helena (2009)
Turbinella laevigata is found since the intertidal zone up to 40 m depth, being endemic of Brazil where it occurs from the state of Amapá to the state of Espirito Santo. The objective of this study was to describe the ootheca of this species. Fifteen samples collected in the Olho d'Água Beach, City of Icapuí and Fleixeiras Beach, City of Trairí, both in Ceará State, Northeast Brazil, were studied. The spawns were composed by 15 +/- 1.4 SD capsules and had 63 +/- 6.4 SD mm of length with 41 +/- 2.5 SD mm of width. They had a convex and a concave surface, and plaited edges that drew out until the basal membrane, to which they joined forming a medial ridge. This species apparently produced a high amount of nurse eggs. The early juveniles measured 6.4 +/- 0.7 SD mm of length and they presented a protoconch with three whorls. © 2009 Tecpar.